Report of the Auditor-General of the Federation on the public accounts of North Rhodesia for the financial year ended 30th June, 1963: presented to the legislative assembly 1964 (Lusaka: The Government printer, 1964)
This is a report of the Auditor-General of the Federation of Northern Rhodesia (Zimbabwe) on the public accounts for the year ended 30th June, 1963.
osc 12/04/2019
Arch
Keywords: Economic conditions; Northern Rhodesia (Zambia)